Implementación en software de un sistema de visión artificial para reconocimiento de gestos de la mano, aplicado en la interacción con un sistema simulado del estéreo de un vehículo (2018)
Due to the great technological advance nowadays, man has developed different forms of communication with the machines or electronic devices that abound in society. From systems of didactic use to sophisticated security systems include different methods of communication between man and machine, among which stand out the systems based on artificial vision. This type of systems is based on extracting information from an image and thus generate an action, allowing interaction with different devices. The main objective of this project is to implement in software a system based on artificial vision which can fulfill a function from an order given by a gesture of the human hand, going through the different stages of image processing and artificial vision algorithms. Once the main objective has been achieved, a demonstration will be made in a graphical interface that simulates the stereo of a vehicle, which will be controlled by hand gestures.